Properties of Geopolymer Concrete Using Ultrafine Fly Ash and Nanosilica - Deb, Partha Sarathi (Curtin University, 2018)
This study investigated the effects of ultrafine fly ash and nanosilica in geopolymers cured at room temperature. It was found that the optimum percentages of ultrafine fly ash and nanosilica with fly ash alone or that blended with 15% GGBFS or 10% OPC significantly improved strength and durability of geopolymers. The properties of geopolymer improved by enhancement of the hydrated phases and microstructure that reduced porosity.